Philanthropy in Lithuania: Looking for Modernity in Traditional Society - Vaidelytė, Eglė (Sociologija. Mintis ir veiksmas, 2006)
Philanthropy phenomenon in contemporary Lithuania demonstrates the weakness of philanthropic and civic traditions that occurred due to the gap during communist period. This tendency puts ambiguity to the perception of what is “pure” and “appropriate” form of philanthropic action. During the last century all over the world philanthropic concept has acquired new modern qualities of rationality that largely enriched the traditional philanthropy understanding. The perception of philanthropy as a traditional Christian charity is still dominating in Lithuanian society, nevertheless philanthropic action appears as a combination of traditional altruistic and modern egoistic intentions as the nowadays reality doesn’t allow to avoid modern rational aspects of philanthropy. This paper is dwelling on the analysis of empirical quantitative and qualitative data revealing the philanthropy perception and intentions of philanthropic action among Lithuanian society and philanthropy experts.